SOLUTION OF THE BUFFER ALLOCATION PROBLEM USING THE OVERALL EQUIPMENT EFFECTIVENESS INDICATOR IN A SERIAL PRODUCTION LINE - Hernández-Vázquez, José Omar; Hernández-Vázquez, José Israel; Hernández-González, Salvador; Olivares-Vera, Daniel Arturo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
This paper presents an analysis of the buffer allocation problem on a serial production line with five workstations and four buffer locations with unreliable operating conditions. Originally, this work was used as an optimization criterion to maximize the Overall Equipment Effectiveness indicator; said indicator is used to evaluate the performance of the processes in Lean Manufacturing; a comparison of the generated solution configurations is made with respect to other optimization criteria such as the minimization of the average work-in-process inventory and the maximization of Throughput. Three case studies involving the production line operating in a balanced and unbalanced manner are examined. The evaluation method used in this document is simulation. On the other hand, an exhaustive enumeration of the analyzed solution space is made. The results report the optimal allocation of buffers in the case studies and the differences that exist in the distribution of these in the optimization criteria investigated.